2005
DOI: 10.1038/sj.cdd.4401822
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin G1 overcomes radiation-induced G2 arrest and increases cell death through transcriptional activation of cyclin B1

Abstract: Although cyclin G1 has been implicated in certain p53-related biological phenomena, other aspects of its function remain unclear. Here we report hitherto unknown mechanism by which cyclin G1 increases radiation sensitivity by regulating the level of cyclin B1. Overexpression of cyclin G1 was observable in lung carcinoma tissues. Irradiation of human lung cells with cyclin G1 overexpression resulted in increased cell death and c-H2AX foci suggesting that cyclin G1 rendered the cells more susceptible to DNA dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 32 publications
1
42
0
Order By: Relevance
“…Our results demonstrated that the mRNA expression of cyclin B (CCNB1) and Cdc2 (CDK1) increased by 4-and 2.5-fold, respectively in the A-375 (SASH1) cells compared with the A-375 (EGFP) cells. The G2/M arrest mostly resulted from the inhibition of the expression of cyclin B or Cdc2 (20,21). However, our findings suggested that SASH1 enhanced G2/M arrest via the upregulation of cyclin B and Cdc2.…”
Section: Discussionmentioning
confidence: 50%
“…Our results demonstrated that the mRNA expression of cyclin B (CCNB1) and Cdc2 (CDK1) increased by 4-and 2.5-fold, respectively in the A-375 (SASH1) cells compared with the A-375 (EGFP) cells. The G2/M arrest mostly resulted from the inhibition of the expression of cyclin B or Cdc2 (20,21). However, our findings suggested that SASH1 enhanced G2/M arrest via the upregulation of cyclin B and Cdc2.…”
Section: Discussionmentioning
confidence: 50%
“…Consistent with the notion that CycG2 helps restrict G 2 /M transition, we show for the first time that 1) a caffeine-sensitive but KU55933-insensitive and ATM-independent DDR pathway promotes CycG2 up-regulation during the late phase of doxorubicin-induced G 2 /M checkpoint and 2) that CycG2 depletion attenuates G 2 /M checkpoint-induced down-regulation of Cdc25B, inhibitory phosphorylation of Cdc2, and accumulation of CycB1. Given the report that elevated CycG1 expression promotes transcriptional activation of CycB1 and abrogation of G 2 /M checkpoint arrest (72), it is possible that there is a Yin and Yang relationship between these two G-type cyclins and that CycG2 acts to restrict CycG1-associated activity during DNA damage responses. The single CycG homolog in Drosophila is an essential protein for embryonic development that restricts cell proliferation and growth (85).…”
Section: Discussionmentioning
confidence: 99%
“…For cell-cycle analysis cells were irradiated with doses of 4 to 6 Gy as previously described (19), cells were fixed with 70% ethanol and stained with 10 mg/mL propidium iodide containing 100 mg/mL RNase A. Bromodeoxyuridine (BrdUrd) analysis was performed with the BD Pharmingen BrdUrd Flow Cytometry Kit and the Cell Proliferation ELISA BrdUrd Kit (Roche Applied Science) according to the manufacturer's instruction. Cell-cycle distribution was assessed by FACSCanto (BectonDickinson) and FlowJo (Treestar).…”
Section: Cell-cycle Analysismentioning
confidence: 99%